Expanding the conservation estate in South Africa : the case of Coleske Farm in the Baviaanskloof - McGregor, Eleanor C. (University of the Free State, 2014)
Finding the balance between biodiversity conservation and development imperatives is a global quandary. Integrated Conservation and Development Projects (ICDPs) that seek to link conservation and development are thus being implemented. Conservation Authorities historically purchased Coleske farm to initiate the development of the Baviaanskloof Nature Reserve (BNR) into the Baviaanskloof Mega-reserve (BMR) ICDP. This ICDP has called for the Coleske community to resettle, via the implementation of a previously developed resettlement action plan (RAP), to a development node that could be developed in the BMR ICDP. The purpose of this document is to report on the findings that emerged from the research that explored the broad challenges and impediments in expanding the conservation estate in South Africa by looking at the situation of Coleske farm in the BNR. Exploratory research was undertaken through in-depth semi-structured face-to-face and telephonic interviews with the Coleske community heads of households and key stakeholder organisations. The most important documents pertaining to the situation of Coleske farm were consulted and the findings of the study were compared against the pertinent fundamentals, basics, ideals, principles or guidelines for ICDP implementation in order to extract lessons learnt from the situation of Coleske. The findings show that the general situation of Coleske has deteriorated since the land was purchased for inclusion in the BNR and the pertinent fundamentals for ICDP implementation were not employed from the onset; as a result, efforts and attempts to correct the associated negative consequences retrospectively are proving to be difficult. The document recommends that a coordinated approach to solve the situation at Coleske be employed, that key stakeholders be lobbied and mobilised to take on their respective roles and responsibilities, and that binding decisions be made and implemented in order to ensure that the status quo of Coleske does not remain for years to come. The study concludes that, in order to realise the intention of the Baviaaskloof Mega-reserve ICDP, the fundamental characteristics of an ICDP, i.e., inclusion, partnerships, legitimacy, cohesion, demarcation, resilience, and so forth, would need to be embraced by all the role players and that finalising the situation of Coleske is a tangible possibility if the existing frameworks and policies that are of relevance to the Baviaanskloof Mega-reserve ICDP are seriously considered and implemented by the Eastern Cape Government of South Africa.
Keywords: Script (M.E.M. (Centre for Environmental Management))--University of the Free State, 2014; Nature conservation -- South Africa -- Baviaanskloof; Conservation of natural resources -- South Africa -- Baviaanskloof